Peppino Impastato. History of a symbolic victim (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
On the occasion of the 40th Anniversary of Peppino Impastato’s murder, the section “History and Memory” proposes two contributions. The first one, by Stefania Pellegrini, is the result of the experience of the author as observer during the demonstration organized in Cinisi on the 9th May 2018. The second one instead, by Sarah Mazzenzana, is a selection of excerpts from the Report produced by the working Committee that had investigated on Peppino Impastato’s offence (approved in 2000). The document provides an overall political and historical background within which the murder must be placed, in order to seize and understand all the elements that prevented immediately who ordered and carried out the murder.Keywords: Peppino Impastato, murder, 1978, memory, commemoration